2012
DOI: 10.17305/bjbms.2011.2550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noise exposure on catalase activity of growing lymphocytes

Abstract: Oxidative stress due to noise was estimated at cell level using model of growing lymphocytes. Lymphocytes were isolated and cultured using conventional methodology. Cell culture of each group was exposed to sound of frequency 1 KHz during incubation. Three groups were defined on the basis of exposure of sound with specific range of intensity and duration of exposure. Group A and Group B were exposed to sound with intensity 110 dBA for four hours per day and for eight hours per day respectively. Control group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…com/NCH-Tone-Generator/3000-2169_4-10019045.htmL). 1 KHz frequency of sound was generated and intensity was changed by amplifier to 100 dB, which was confirmed by digital sound level meter before the start of experiment [33] .…”
Section: Methodsmentioning
confidence: 82%
“…com/NCH-Tone-Generator/3000-2169_4-10019045.htmL). 1 KHz frequency of sound was generated and intensity was changed by amplifier to 100 dB, which was confirmed by digital sound level meter before the start of experiment [33] .…”
Section: Methodsmentioning
confidence: 82%
“…Advanced oxidation protein products (AOPP) levels were assessed by spectrophotometric measurement according to the method of Witko-Sarsat et al,8 and the results are reported as chloramine-T equivalents. Other parameters, measured by commercial enzyme-linked immunosorbent assay kits (USCN Life Science Inc. Wuhan, China) according to the manufacturer's instructions as previously reported,9-11 included catalase, 8-hydroxydeoxyguanosine (8-OHdG), and malondialdehyde (MDA).…”
Section: Methodsmentioning
confidence: 99%